Expose the bioactive properties of Picrorhiza kurroa root extract oil (PKEO): phytochemical composition and therapeutic activities - Patil, Amol R.; Maru, Avish D. (Journal of Applied Pharmaceutical Research, 2024)
Background: The present study aims to explore the bioactive properties of essential Oil (PKEO) derived from Picrorhiza kurroa (commonly known as kutki), a medicinal plant known for its therapeutic potential. Picrorhiza kurroa essential oil has a distinct chemical profile, which sets it apart from other essential oils. The bioactive compounds present in Picrorhiza kurroa essential oil may lead to the development of new drugs, particularly for treating inflammatory and oxidative stress-related disorders. The research aims to study the extraction, phytochemical composition, and various biological activities of PKEO. Methodology: Oil obtained through hydro-distillation contains various phytochemical compounds, including steroids, triterpenoids, alkaloids, phenols, proteins, flavonoids, and tannins. Its bioactivity and aroma are attributed to its phenolic and sesquiterpene esters. Results and Discussion:  The total phenolic content is 250.47 μg GAE/g, and the total flavonoid content is 245.26 μg QE/g. UV-visible and IR spectroscopic analyses confirm the presence of phenolic and terpenoid ester functional groups. PKEO has moderate antioxidant activity, with IC50 values of 98.19 µg/mL in DPPH scavenging and 42.72% inhibition in the ABTS assay. It also exhibits dose-dependent inhibition of protein denaturation and HRBC stabilizing activity. Antimicrobial tests show PKEO inhibits E. coli growth, indicating potential antibacterial properties. Conclusion: These findings highlight PKEO's promising bioactive profile, suggesting potential therapeutic and cosmetic formulation applications. The antifungal activity also shows the potential antifungal effects of the PKEO.